Italians and Food - Sassatelli, Roberta (Consumption and Public Life,, 2019)
This book is a novel and original collection of essays on Italians and food. Food culture is central both to the way Italians perceive their national identity and to the consolidation of Italianicity in global context. More broadly, being so heavily symbolically charged, Italian foodways are an excellent vantage point from which to explore consumption and identity in the context of the commodity chain, and the global/local dialectic. The contributions from distinguished experts cover a range of topics including food and consumer practices in Italy, cultural intermediators and foodstuff narratives, traditions of production and regional variation in Italian foodways, and representation of Italianicity through food in old and new media. Although rooted in sociology, Italians and Food draws on literature from history, anthropology, semiotics and media studies, and will be of great interest to students and scholars of food studies, consumer culture, cultural sociology, and contemporary Italian studies.